Soil legacy phosphorus after 10 years of annual dairy liquid manure application in a no‐tillage system. (26th December 2022) - Gotz, Lenir Fátima; Favaretto, Nerilde; Barth, Gabriel; Pavinato, Paulo Sergio; Pauletti, Volnei
Abstract: The benefits of manure as a source of nutrients for plants and to improve soil quality are well‐known. Monitoring of manure application is needed if environmental issues are to be prevented. In particular, the availability and accumulation of phosphorus (P) has to be subject to rigorous monitoring. This study aims to both evaluate the efficacy of the resin method in extracting inorganic labile P in soils under the long‐term application of dairy liquid manure (DLM), and verify the influence of DLM on the recovery of applied P and soil legacy P. To realize our objectives, two long‐term field experiments were established under a no‐tillage system with annual DLM application on sandy clay loam (sandy Oxisol) and clayey (clayey Oxisol) soils. Treatment consisted of DLM applications (0, 60, 120, 180 m 3  ha −1  year −1 ), independent of mineral fertilizer. Soil samples were taken from the 0–5, 5–10 and 10–15 cm layers after 10 years from the beginning of the trial. A single extraction with resin underestimated inorganic labile P; however, successive extractions were able to take up 43% and 26% of the total P in sandy and clayey Oxisols, respectively, whereas in a single extraction the take‐up was 17% and 8% from the same soils, respectively. The resin method was more effective in extracting P from the sandy Oxisol. Thus, when interpreting soil P contents for fertilizer planning, the soil texture should be taken into account. DLM application decreased P recovered from applied P, ranging from 54% to 83% (sandy), and 43% to 67% (clayey), and substantially increased soil legacy P.